Foundations of modern statistics festschrift in honor of Vladimir Spokoiny, Berlin, Germany, November 6-8, 2019 - Spokoiny, S. G. (Springer proceedings in mathematics & statistics, volume 425)
This book contains contributions from the participants of the international conference Foundations of Modern Statistics which took place at Weierstrass Institute for Applied Analysis and Stochastics (WIAS), Berlin, during November 68, 2019, and at Higher School of Economics (HSE University), Moscow, during November 30, 2019. The events were organized in honor of Professor Vladimir Spokoiny on the occasion of his 60th birthday. Vladimir Spokoiny has pioneered the field of adaptive statistical inference and contributed to a variety of its applications. His more than 30 years of research in the field of mathematical statistics had a great influence on the development of the mathematical theory of statistics to its present state. It has inspired many young researchers to start their research in this exciting field of mathematics. The papers contained in this book reflect the broad field of interests of Vladimir Spokoiny: optimal rates and non-asymptotic bounds in non parametrics, Bayes approaches from a frequentist point of view, optimization, signal processing, and statistical theory motivated by models in applied fields. Materials prepared by famous scientists contain original scientific results, which makes the publication valuable for researchers working in these fields. The book concludes by a conversation of Vladimir Spokoiny with Markus Rei and Enno Mammen. This interview gives some background on the life of Vladimir Spokoiny and his many scientific interests and motivations.